A case of asymptomatic pancytopenia with clinical features of hemolysis as a presentation of pernicious anemia. Issue 4 (1st January 2016) - Kollipara, Venkateswara K.; Brine, Patrick L.; Gemmel, David; Ingnam, Sisham
Abstract : Pernicious anemia is an autoimmune disease with a variety of clinical presentations. We describe a case of pernicious anemia presenting with pancytopenia with hemolytic features. Further workup revealed very low vitamin B12 levels and elevated methylmalonic acid. It is important for a general internist to identify pernicious anemia as one of the cause of pancytopenia and hemolytic anemia to avoid extensive workup. Pernicious anemia can present strictly with hematological abnormalities without neurological problems or vice versa as in our case.